2011
DOI: 10.1111/j.1600-9657.2011.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term antimicrobial properties of mineral trioxide aggregate with incorporated silver-zeolite

Abstract: The purpose of this in vitro study was to determine whether adding silver-zeolite (SZ) to mineral trioxide aggregate (MTA) would enhance the antimicrobial activity of MTA against Staphylococcus aureus (ATCC #25923), Enterococcus faecalis (ATCC #29212), Escherichia coli (ATCC#25922), Pseudomonas aeruginosa (ATCC #27853), Candida albicans (ATCC #90028), Porphyromonas gingivalis (ATCC #33277), Actinomyces israelii (ATCC #12102), and Prevotella intermedia (ATCC# 15032). SZ was added at 0.2% and 2% mass fraction co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
(81 reference statements)
2
48
0
1
Order By: Relevance
“…The antimicrobial effect of IRM could be explained by the antibacterial ability of eugenol released from IRM by progressive hydrolysis [38]. No antibacterial effect of MTA against P. ginigivalis was observed in the current study, which is consistent with previous studies [30,39]. All tested cements caused significant but limited reduction on E. faecalis growth ranging from 2-15% compared to control.…”
Section: Discussionsupporting
confidence: 90%
“…The antimicrobial effect of IRM could be explained by the antibacterial ability of eugenol released from IRM by progressive hydrolysis [38]. No antibacterial effect of MTA against P. ginigivalis was observed in the current study, which is consistent with previous studies [30,39]. All tested cements caused significant but limited reduction on E. faecalis growth ranging from 2-15% compared to control.…”
Section: Discussionsupporting
confidence: 90%
“…The antimicrobial activity evaluation showed similar results for all the microorganisms evaluated. The addition of substances to MTA aiming to improve its antimicrobial effect has been studied [27][28][29] . Odabas et al 29) demonstrated that silver addition to MTA improves its antimicrobial property.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of substances to MTA aiming to improve its antimicrobial effect has been studied [27][28][29] . Odabas et al 29) demonstrated that silver addition to MTA improves its antimicrobial property. Saatchi 27) et al observed that the inclusion of potassium iodide does not alter the antimicrobial effect of MTA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been showed that incorporating SZ into MTA was sufficient for enhancing its antimicrobial activity 16) . However, there was no study to evaluate the influence of SZ on chemical and physical properties of MTA.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro previous study showed favourable antimicrobial effects of MTA containing SZ on several microorganisms. It also has been clarified that incorporated SZ increased the antimicrobial properties of MTA 16) . However it is very important that physicochemical properties of MTA containing SZ be considered in relation to their use because such filling material should present biocompatibility, adequate setting time, insolubility and antimicrobial activity 17) .…”
Section: Introductionmentioning
confidence: 99%